2018
DOI: 10.1002/bab.1708
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and reactive oxygen species scavenging properties of cellular albumin in HepG2 cells is mediated by the glutathione redox system

Abstract: This study was carried out to examine the role of intracellular albumin in the modulation of oxidative damage induced by glutathione modifiers in HepG2 cells. Also, the relationship of albumin synthesis with oxidative stress factors including antioxidants was studied. HepG2 cell culture was supplemented with glutathione modifiers; L-Buthionine-sulfoximine (BSO; 0.1 and 1.0 mM) or N-acetyl cysteine (NAC; 1 and 10 mM) and the cell viability and changes in reduced glutathione (GSH), oxidized glutathione (GSSG), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…7I). The results showed the increase in ROS and decrease in △Ψm could be inhibited by supplementing with GSH (10 mM) after hypoxia 35 . However, the effect of Drp1 shRNA treatment on mitochondrial function was more pronounced after hypoxia.…”
Section: Drp1 Participates In Cellular Metabolic Disorders After Ischmentioning
confidence: 95%
See 1 more Smart Citation
“…7I). The results showed the increase in ROS and decrease in △Ψm could be inhibited by supplementing with GSH (10 mM) after hypoxia 35 . However, the effect of Drp1 shRNA treatment on mitochondrial function was more pronounced after hypoxia.…”
Section: Drp1 Participates In Cellular Metabolic Disorders After Ischmentioning
confidence: 95%
“…However, the effect of Drp1 shRNA treatment on mitochondrial function was more pronounced after hypoxia. We also used GSH inhibitor buthionine sulfoxamine (BSO) (1 mM) 35,36 on the basis of Drp1 shRNA treatment and found that the ROS level increased by 28% and △Ψm decreased by 20% ( Fig. 7I-J).…”
Section: Drp1 Participates In Cellular Metabolic Disorders After Ischmentioning
confidence: 99%
“…It can be inferred that ECM composition does not directly affect the albumin and urea release of hepatocytes in a dynamic cell culture environment. It has been found that intracellular albumin has superior diagnostic value, and its concentration may differ for extracellular albumin [ 34 ]. To determine the impact of ECM composition on intracellular albumin expression, hepatocytes were stained for intracellular localization of albumin via immunofluorescence staining.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress damages the nerve cells in many neurodegenerative and other diseases (17)(18)(19)(20). Attenuation of oxidative stress increases the survival of NSCs after transplantation into the affected area of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%